2007
DOI: 10.1038/ncb1652
|View full text |Cite
|
Sign up to set email alerts
|

Spatial regulation of Fus3 MAP kinase activity through a reaction-diffusion mechanism in yeast pheromone signalling

Abstract: Signal transduction through mitogen-activated protein kinase (MAPK) cascades is thought to occur through the assembly of macromolecular complexes. We quantified the abundance of complexes in the cytoplasm among the MAPKs Ste11, Ste7, Fus3 and the scaffold protein Ste5 in yeast pheromone signalling using fluorescence cross-correlation spectroscopy (FCCS). Significant complex concentrations were observed that remained unchanged on pheromone stimulation, demonstrating that global changes in complex abundances do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
223
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(228 citation statements)
references
References 31 publications
4
223
0
1
Order By: Relevance
“…The high contribution (48%) can be explained taking the presence of non-matured mCherry into account. Maeder and co-workers used a similar construct with a different linker in yeast and found that 50% of mCherry is not matured (Maeder et al 2007). Non-matured mCherry contains green chromophores, which are different from EGFP and with shorter fluorescence lifetimes (Cotlet et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The high contribution (48%) can be explained taking the presence of non-matured mCherry into account. Maeder and co-workers used a similar construct with a different linker in yeast and found that 50% of mCherry is not matured (Maeder et al 2007). Non-matured mCherry contains green chromophores, which are different from EGFP and with shorter fluorescence lifetimes (Cotlet et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Spatial gradients of protein activities organize signaling around cellular structures, such as membranes, chromosomes and scaffolds, and provide positional cues for key processes, including cell division. Such intracellular gradients of protein activities have been detected in live cells using imaging technologies based on fluorescence resonance energy (Maeder et al 2007). …”
Section: Spatial Signal Propagationmentioning
confidence: 99%
“…This lack of temporal resolution prevented to investigate whether mitochondrial permeabilization is subject to spatial coordination by processes such as localized production of signaling molecules and/or diffusion, which were previously described as important regulators of other cellular signaling pathways, such as the forwarding of phosphorylation signals and Ca 2 þ waves. [15][16][17] We here describe a novel approach combining rapid cellular imaging and computational modeling to remedy this limitation in the analysis of apoptotic signaling. Taking advantage of the synchrony of sibling cells in apoptosis onset, we established an imaging technique that is capable of predicting the time of MOMP for individual cells with high probability.…”
mentioning
confidence: 99%